Enhancement of a Stepping Stone Detection Algorithm Using Data Mining and Associate Rule Techniques (S/O: 12896) - Omar, Mohd Nizam; Ghazali, Osman; Daud, Ali Yusny; Azzali, Fazli (UUM, 2020)
Stepping stone listed as one of the technique that most used by an intruder to hide their tracks. After more than a decade, researcher focused to enhance the stepping stone detection approach as to obtain compromised stepping stone detection, none of these research that really solve the stepping stone problem. Less accurate detection and Active Perturbation Attack (APA) is the most problem that becomes a threat to SSD approach itself. By using hybrid approach to increase an accurate detection and intelligent technique to overcome the APA problem, this research proposed the combination of hybrid and intelligent SSD to as create Hybrid Intelligent SSD (HI-SSD). Through extensive experiment to steps that have been identified to create complete HISSD, experiment not only produce a plain result, but also at the same time comparison on the most related approach has been made. Through the final experiment that combined hybrid and intelligent approach, it shows that the proposed approach (HI-SSD) not only better in accuracy but also robust towards APA attack. Compare to other related research, HI-SSD produced 0 % FPR and 100% TPR. By the execution of this research, SSD-based research is more robust against APA problem that has been identified unsolved over fourteen years